Avaliação da instrumentação endodôntica com limas rotatórias para dentes decíduos em comparação a limas manuais e limas rotatórias convencionais - Análise em microtomografia computadorizada - Heinz, Gustavo Henrique Istoski (2024)
Deciduous teeth should be preserved until their physiological exfoliation. Pulpectomy is an option for their maintenance but is a challenging procedure due to the required clinical time and the patient’s behavioral cooperation. The use of rotary systems may reduce clinical time. Objectives: To evaluate the root canal wall wear and volumetric changes in the root canal of artificial deciduous teeth after instrumentation with manual files and two rotary file systems, one specifically designed for deciduous teeth. Methodology: A total of 36 prototyped artificial maxillary deciduous molars were used, focusing on the distobuccal root. The teeth were divided into three instrumentation groups: Sequence Baby-File (SBF), ProDesign Logic 2 (LOGIC), and manual K-files (MANUAL). The specimens were scanned using micro-computed tomography before and after instrumentation to assess root canal wall wear and volumetric changes. Statistical analysis was performed using BioEstat 5.3 software (Kolmogorov-Smirnov, ANOVA, Tukey, Kruskal-Wallis, and Dunn tests, p>0.05). Results: The volumetric increase in the canal was lower with LOGIC (15.0%), followed by SBF (29.4%) and MANUAL (35.3%), with a significant difference between LOGIC and MANUAL systems (p=0.0010). There were no statistically significant differences between the systems (p=0.502) in terms of root canal wall thickness loss. Conclusion: The three systems did not differ in terms of root canal wall wear after instrumentation. However, the manual system showed a greater increase in canal volume compared to the rotary systems.